2004
DOI: 10.1074/jbc.m312289200
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic Acid Protects Efficiently Only against a Specific Form of Peroxynitrite-induced Damage

Abstract: The ability of the sulfur-containing compounds glutathione (GSH), glutathione disulphide (GSSG), S-methylglutathione (GSMe), lipoic acid (LA), and dihydrolipoic acid (DHLA) to protect against hypochlorous acid (HOCl)-mediated damage and peroxynitrite (ONOOH)-induced damage has been compared. Protective activity was assessed in competition assays by monitoring several detectors, i.e. dihydrorhodamine-123 (DHR-123) oxidation, ␣ 1 -antiproteinase (␣ 1 -AP) inactivation, and glutathione S-transferase P1-1 (GST-P1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…Lipid peroxides and peroxynitrite have both been implicated as the oxidants that oxidize ferric heme to a ferryl-oxo protoporphyrin radical (40). Previous reports have shown that LA can regenerate endogenous and exogenous antioxidants and scavenge free radicals, including lipid peroxides and peroxynitrite, in cells (13,41,42). Thus, this antioxidant property of LA may be involved in the inhibition of COX-2 and the subsequent decrease in PGE 2 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxides and peroxynitrite have both been implicated as the oxidants that oxidize ferric heme to a ferryl-oxo protoporphyrin radical (40). Previous reports have shown that LA can regenerate endogenous and exogenous antioxidants and scavenge free radicals, including lipid peroxides and peroxynitrite, in cells (13,41,42). Thus, this antioxidant property of LA may be involved in the inhibition of COX-2 and the subsequent decrease in PGE 2 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Hypochlorous acid scavenging assay. HOCl was measured by using a previously described fluorescent methodology, 54 based on the HOCl-induced oxidation of DHR to rhodamine 123, which has been adapted to a microplate reader. HOCl was prepared immediately before use by adjusting the pH of a 1% (m/v) solution of NaOCl to 6.2 with dropwise addition of 10% H 2 SO 4 .…”
Section: 32mentioning
confidence: 99%
“…The 2 sulfur atoms in the 1,2-dithiolane ring confers upon LA a high tendency for reduction of other redox-sensitive molecules. In contrast, the presence of 2 - SH groups in DHLA makes it more effective, on a molar basis, than glutathione (GSH) or N-acetylcysteine in protecting against α1-antiproteinse [8,9,10,11,12,13,14]. …”
Section: Chemical Structures Of Lamentioning
confidence: 99%
“…The molecule α-LA (1,2-dithiolane-3-pentanoic acid) naturally exists in both prokaryotic and eukaryotic cells. Studies have shown that both α-LA and DHLA efficiently protect against cellular damage by peroxynitrite [9,12,13]. Moreover, peroxynitrite-derived carbonate and nitrogen dioxide radicals readily react with α-LA and DHLA [14].…”
Section: Antioxidant Functions Of Lamentioning
confidence: 99%
See 1 more Smart Citation